Mitigating water stress in wheat (Triticum aestivum L.) with biochar application - Naresh Kumar; S. K. Intodia; Naleeni Ramawat (Annals of Agricultural Research, 2024)
A field experiment was conducted at Rajasthan College of Agriculture (MPUAT), Udaipur (Rajasthan) during Rabi season of 2021-22 with four levels of water stress as main-plot and four levels of biochar as sub-plot in Split Plot Design (SPD) replicated thrice. The water stress at tillering significantly decreased plant height, dry matter accumulation and number of tillers at 60, 90 DAS and at harvest over control. The dry matter accumulation and total number of tillers at harvest were also reduced due to water stress at grain filling stage. Similarly, yield attributes, grain, straw and biological yields were significantly reduced due to water stress during critical stages. The yields were significantly improved with biochar application @ 3 and 4 t ha- 1over control which resulted to increase in grain yield by 12.28 and 13.00 per cent, respectively, over control (4837 kg ha-1).